2019
DOI: 10.1136/bcr-2019-230007
|View full text |Cite
|
Sign up to set email alerts
|

Acute epididymo-orchitis frombrucellosis melitensisin Australia

Abstract: Brucellosis epididymo-orchitis (BEO) is extremely rare in non-endemic areas such as Australia. While epididymo-orchitis is relatively common in adolescent men, when presented with a significant travel history, consideration should be given to rare causes such as this. Here, we present a case of BEO in a young 18-year-old man who recently migrated from Greece, with symptoms of acute scrotal pain, swelling and persistent fever. Brucella melitensis was isolated in the blood culture and confirmed with PCR. We susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…These complications have been rarely reported in patients with brucellosis (24,25). Also, in our study, epididymo-orchitis presented with testicular pain and dysuria, as reported in previous studies (26).…”
Section: Discussionsupporting
confidence: 87%
“…These complications have been rarely reported in patients with brucellosis (24,25). Also, in our study, epididymo-orchitis presented with testicular pain and dysuria, as reported in previous studies (26).…”
Section: Discussionsupporting
confidence: 87%
“…Currently, B. suis is the only cause of endemic brucellosis in Queensland due to human killing and handling of feral pig carcasses. Other human cases of brucellosis were imported from endemic countries such as Mediterranean, Middle East, and Latin American countries [ 50 ]. In addition, only 19 human cases were reported in New Zealand between 2007 and 2019.…”
Section: Oceaniamentioning
confidence: 99%